An Analysis Of Perlocutionary Acts In The Movie "Shang-Chi And The Legend Of The Ten Rings" - Gitasyah A Kaaba; Rahman Taufiqrianto Dako; Jefriyanto Saud (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study analyzes the types of perlocutionary acts found in the movie Shang-Chi and the Legend of the Ten Rings. The objective of the study is to identify and describe how utterances spoken by the characters produce observable effects on hearers. This research applies to a descriptive qualitative method because the data are in the form of words, scenes, contexts, and hearer responses rather than numerical measurement. The primary data consist of selected utterances from the movie, while the supporting data are taken from books and previous studies on pragmatic and speech acts. The data were collected through observation, transcription, note-taking, and purposive selection. The analysis was conducted by identifying the context, classifying the perlocutionary effect, and interpreting the hearer response. The findings show 26 perlocutionary data points from 25 dialogic contexts. Five types are identified: persuading, convincing, inspiring, intimidating, and insulting. Persuading appears as the dominant type because the movie contains many urgent action scenes, commands, warnings, and emotional appeals that directly influence the hearers.